Treatment of gorham-stout disease with bisphosphonates and total hip arthroplasty: A case report - Zhang, LiQian; Li, JianJian; Yao, Fei; Chen, YiHao; Zhang, Shuo; Lv, Hao; Jing, JueHua (Frontiers in Surgery, 2023)
Background: Gorham-Stout disease (GSD) is a rare osteolytic disease with unknown etiology, varied clinical manifestations and unpredictable prognosis. This disease is characterized by progressive massive local osteolysis and resorption caused by intraosseous lymphatic vessel structure and thin-walled vascular proliferation. The diagnosis of GSD has not yet formed a uniform standard, but the combination of clinical manifestations, radiological features and unique histopathological examinations and excluding other diseases contribute to early diagnosis. Although medical therapy, radiotherapy and surgical interventions or combinations have been used for the treatment of GSD, there is currently still no recommended standardized treatment regimen. Case report: This paper presents a case of a previously healthy 70-year-old man presented with a 10-year history of severe right hip pain and progressive walking disorder of the lower limbs. Based on the patient's clear clinical presentation, unique radiological features, and histological findings, a diagnosis of GSD was made with the exclusion of other potential diseases. The patient was treated with bisphosphonates to slow the progression of the disease followed by total hip arthroplasty to help restore walking function. At the 3-year follow-up, the patient returned to normal walking and no recurrence was observed. Conclusion: Bisphosphonates combined with total hip arthroplasty may be an effective method for the treatment of severe GSD in the hip joint. may provide a reference to cure GSD in the future. KEYWORDS: Gorham-Stout disease, bisphosphonates, arthroplasty, hip joint, histopathological, radiological features